Faculty and student research in practicing academic freedom - Sengupta, Enakshi; Blessinger, Patrick (Innovations in higher education teaching and learning ;, 2020)
Events in recent years, including instances in which academics have been jailed for protesting against corrupt political regimes, have demonstrated that the concept of academic freedom is under threat. Presenting case studies which reveal real-life examples of enforced silence, this book examines the concept of academic freedom in the context of globalization and outlines the challenges posed to the development of higher education. Offering a balanced view, which also showcases positive improvements in transparency and accountability, the authors examine the role of racial and gender biases, paired against rights and responsibilities, to highlight the drivers of restrictions on academic freedom. Including case studies from Turkey, Iraq, Pakistan and Hungary, along with examples of interventions and programmes intended to uphold freedom values, this volume provides a comprehensive overview of the challenges and potential solutions to securing and practicing academic freedom.